Evaluation of the Prevalence of Maxillary Sinuses Abnormalities through Spiral Computed Tomography (CT) - Drumond,João Paulo Nunes (2017)
Abstract Introduction Maxillary sinus disease is common and numerous disorders can affect this anatomical area. Abnormalities can be classified as: non-neoplastic, neoplastic benign, and neoplastic malignant. Objective Evaluate through CT the prevalence of diseases in maxillary sinuses, using the Radiology Department’s database of a hospital in São Paulo city. Methods The sample consisted of 762 facial CT scans that we divided into three groups: Group A (12-19 years old); Group B (20-49 years old); Group C (above 50 years old); and male or female. We considered the following pathological processes: I - Mucoperiosteal Thickening; II - Chronic Sinusitis; III - Chronic Odontogenic Sinusitis; IV - Rhinosinusitis; V - Polypoid Lesions; VI - Bone Lesions; VII - Neoplasms; VIII - Antrolith; IX - Foreign Bodies; X - Oroantral Fistula. Results Our study found that 305 exams (40.02%) were normal and 457 exams (59.97%) were abnormal. We found the following disease frequencies: focal mucoperiosteal thickening (21.25%); polypoid lesions (10.76%); chronic sinusitis (7.48%); chronic odontogenic sinusitis (2.29%); neoplasms (2.03%); rhinosinusitis (1.77%); bone lesions, foreign bodies and oroantral fistula in 0.65%; 0.13% and 0.06% respectively. There was no significant difference between male and female, and Groups A, B, or C when relating the frequencies of abnormalities found. There was no significant difference between male and female and the age group for the side of the altered maxillary sinus. Conclusion We observed a high prevalence of sinus maxillary diseases. Mucoperiosteal thickening; acute, chronic, and odontogenic sinusitis; polypoid lesions and neoplasms have high prevalence in maxillary sinuses. Thus, facial CT exam was effective for the evaluation of diseases in maxillary sinuses.